Genotypic and phenotypic data for Rice hoja blanca disease resistance QTL analysis - Silva Cordoba, Elkin Alexander; Montoya Pizarro, Maria Elker; Quintero Valencia, Constanza Maria; Cuasquer Sedano, Juan Bosco; Tohme, Joseph M.; Graterol Matute, Eduardo Jose; Cruz, Maribel; Lorieux, Mathias (2023)
These data can be used to search for quantitative trait loci (QTLs) for resistance to the Rice hoja blanca disease: